Emotional health, support, and self‐efficacy in young adults with a history of language impairment. (25th May 2016) - Botting, Nicola; Durkin, Kevin; Toseeb, Umar; Pickles, Andrew; Conti‐Ramsden, Gina
Abstract : Children and adolescents with language impairment (LI) are at risk of emotional health difficulties. However, less is known about whether these difficulties continue into adulthood for this group, or about the potential role of environmental resources (e.g., social support) or internal resources (e.g., self‐efficacy). This study investigates emotional health in 81 adults with a history of developmental LI (aged 24) compared with 87 age‐matched peers (AMPs) using Beck Inventories. Social support and self‐efficacy measures were examined as predictors. The results were fourfold: (1) adults with LI had higher levels of emotional health problems; (2) whilst the availability of social support was similar across groups, people with LI received more help from others compared to peers; (3) social support was not significantly related to emotional health in those with LI – in contrast, for AMPs, uptake of support indicated poorer emotional health; (4) self‐efficacy was the strongest predictor of emotional health in both groups and fully mediated the relationship between language and emotional health (no moderation by group). This cross‐sectional study has implications for concurrent factors that might affect emotional health outcomes for children and young people with and without LI.